2004
DOI: 10.1074/jbc.m402513200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Snapin and Three Novel Proteins (BLOS1, BLOS2, and BLOS3/Reduced Pigmentation) as Subunits of Biogenesis of Lysosome-related Organelles Complex-1 (BLOC-1)

Abstract: Biogenesis of lysosome-related organelles complex-1 (BLOC-1) is a ubiquitously expressed multisubunit protein complex required for the normal biogenesis of specialized organelles of the endosomal-lysosomal system, such as melanosomes and platelet dense granules. The complex is known to contain the coiled-coil-forming proteins, Pallidin, Muted, Cappuccino, and Dysbindin. The genes encoding these proteins are defective in inbred mouse strains that serve as models of Hermansky-Pudlak syndrome (HPS), a genetic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
231
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 234 publications
(248 citation statements)
references
References 45 publications
16
231
0
1
Order By: Relevance
“…The BLOC‐1 complex belongs to the endosomal protein sorting machinery and was first identified through its association with Hermansky–Pudlak syndrome (HPS), a group of heterogeneous autosomal‐recessive disorders caused by mutations in genes affecting the biogenesis of lysosomal‐related organelles (LROs). BLOC‐1 is an octameric complex containing two stable sub‐complexes, pallidin‐Cappuccino‐BLOS1 and dysbindin‐Snapin‐BLOS2 (Starcevic & Dell'Angelica, 2004). We examined the effect of BLOC‐1 subunits on HIV‐1 trans ‐infection and found that knockdown of four members, specifically muted, dysbindin, BLOS3, and the dynein motor protein Snapin had a significant effect on HIV‐1 trans ‐infection (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The BLOC‐1 complex belongs to the endosomal protein sorting machinery and was first identified through its association with Hermansky–Pudlak syndrome (HPS), a group of heterogeneous autosomal‐recessive disorders caused by mutations in genes affecting the biogenesis of lysosomal‐related organelles (LROs). BLOC‐1 is an octameric complex containing two stable sub‐complexes, pallidin‐Cappuccino‐BLOS1 and dysbindin‐Snapin‐BLOS2 (Starcevic & Dell'Angelica, 2004). We examined the effect of BLOC‐1 subunits on HIV‐1 trans ‐infection and found that knockdown of four members, specifically muted, dysbindin, BLOS3, and the dynein motor protein Snapin had a significant effect on HIV‐1 trans ‐infection (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Tyrp1 was enriched at the surface of BLOC-1-deficient melanocytes relative to controls, as shown by IFM analysis of primary melanocytes labeled for Tyrp1 before fixation (Figure 6a) and quantitated by flow cytometry of melan-mu and melan-rp cells relative to BLOC-1-reconstituted cells ( Figure 6b; the more modest Tyrp1 surface expression in melan-rp relative to melan-mu likely reflects residual BLOC-1 activity in rp cells; Starcevic and Dell'Angelica, 2004; our unpublished data). Nevertheless, BLOC-1-deficient cells had lower total cellular Tyrp1 levels (ϳ60% that of BLOC-1-reconstituted cells; Figure 6c), indicating that the increased surface levels reflect Tyrp1 missorting and not increased expression; the decreased Tyrp1 cellular levels in these immortalized BLOC-1-deficient melanocytes may reflect dysregulated expression, because Tyrp1 half-life, measured by metabolic pulse/chase analysis, was unchanged compared with controls (our unpublished data).…”
Section: Bloc-1 Prevents Biosynthetic Delivery Of Tyrp1 To the Cell Smentioning
confidence: 99%
“…The genes disrupted in human HPS-7 (Li et al, 2003) and HPS-8 (Morgan et al, 2006) and in the mouse HPS models pallid, muted, reduced pigmentation (rp), cappuccino, and sandy encode five of the eight known subunits of a stable protein complex known as biogenesis of lysosome-related organelles complex (BLOC)-1 (Falcon-Perez et al, 2002;Moriyama and Bonifacino, 2002;Ciciotte et al, 2003;Li et al, 2003;Gwynn et al, 2004;Starcevic and Dell'Angelica, 2004). To date, no specific subcellular function has been assigned to BLOC-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GST-OCA2 fusion constructs were expressed in Escherichia coli and purified as described previously (Starcevic and Dell'Angelica, 2004). Detergent extracts of MNT-1 or HeLa cells were prepared in MNT-1 buffer (0.1 M Tris-HCl, pH 7.5, 0.15 M NaCl, 1 MgCl 2 , 1 mM NaF, and 0.5% NP-40) or HeLa buffer (25 mM HEPES, pH 7.4, 0.15 M NaCl, 1 mM EDTA, 1 mM NaF, 0.5 mM MgCl 2 , and 0.5% Triton X-100), respectively, containing protease inhibitor mixture [1 mM 4-(2-aminoethyl)-benzenesulfonyl fluoride, 10 g/ml leupeptin, 5 g/ml aprotinin, and 1 g/l pepstatin A].…”
Section: Glutathione Transferase (Gst) Pull-down Assaysmentioning
confidence: 99%